A study of the parameters that determine the reactivity of sugarcane bagasse ashes (SCBA) for use as a binder in construction - Pavia, Sara (My University, 2020)
This paper intends to contribute to the use of waste, as binder replacement, to lower the negative environmental impact of construction. Sugarcane bagasse ash (SCBA) is an agricultural waste which has been reported as pozzolanic. However, the literature on the pozzolanic activity of SCBA is inconclusive. This paper attempts to establish the properties that determine reactivity the most, in an effort to standardise the material, to allow a wider intake into mainstream construction. The fineness, specific surface area, microstructure, composition and amorphousness of ashes from four producers in Brazil are studied, and the microstructure and kinetics of reactions in ash/hydrated-lime pastes investigated with SEM/EDS. The results evidence that, despite their high crystallinity and carbon content, the ashes are pozzolanic. Reactivity was proven with physical (activity index) and chemical tests (conductivity), and hydrates were evident at 7 days. Reactivity increased with rising specific surface area, amorphousness and fineness, but the specific surface area of the particles impacts reactivity the most. This was concluded form the following findings: Fineness is not vital for reactivity, as some coarse ashes produce similar strengths and combine comparable amounts of lime than much finer ashes. The presence of a significant amorphous fraction is not vital for reactivity, as the ashes are active despite consisting mostly of crystalline phases (quartz, corundum and hematite). High carbon contents do not eradicate reactivity, as the ashes with the greatest carbon are the most reactive, achieving the highest strengths and combining the most lime. Finally, all the SCB ashes present a marginal content of anions and alkalis capable of forming detrimental gels and salts, a desirable quality for any pozzolanic material.
Keywords: Sugarcane bagasse ash; Reactivity; Specific surface area; Amorphousness; Fineness; Carbon content; Nanoscience & Materials